2023
DOI: 10.1109/temc.2023.3326190
|View full text |Cite
|
Sign up to set email alerts
|

Transient Magnetic Shielding of a Planar Conductive Thin Screen via Exact Image Theory

Giampiero Lovat,
Paolo Burghignoli,
Rodolfo Araneo
et al.

Abstract: The exact image theory is here applied to study the transient shielding effectiveness of a canonical shielding configuration, i.e., a small current loop in the presence of a parallel planar thin conductive sheet. In particular, the Green function providing the electromagnetic field produced by a pulsed vertical magnetic dipole in the whole space is derived in a closed analytical form. The recently introduced definitions of transient shielding effectiveness are used to evaluate the shielding properties of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…It is next demonstrated that (a corrected version of) this result can be readily deduced from several previously published papers on the subject (not referenced in [1]). Indeed, the pulsed EM signal transmission via a conductive sheet is described in [2], where the plasmonic behavior of conduction electrons in the metal has been additionally accounted for.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…It is next demonstrated that (a corrected version of) this result can be readily deduced from several previously published papers on the subject (not referenced in [1]). Indeed, the pulsed EM signal transmission via a conductive sheet is described in [2], where the plasmonic behavior of conduction electrons in the metal has been additionally accounted for.…”
Section: Introductionmentioning
confidence: 86%
“…The problem configuration (see Fig. 1) under consideration is essentially identical to the one analyzed in [1], [2], [3], for instance. It consists of a horizontal transmitting loop, L T , and a receiving loop, L R , that are separated by a thin highly conducting sheet of thickness δ and conductivity σ.…”
Section: Problem Description and Its Solutionsmentioning
confidence: 99%
See 3 more Smart Citations